Bites by the night adder (Causus maculatus) and burrowing vipers (genus Atractaspis) in Nigeria. - Warrell, D; Ormerod, L; Davidson, N (1976)
Nineteen patients proven to have been bitten by the small African adders Causus maculatus, Atractapis dahomeyensis and A. microlepidota were studied in the Nigerian savanna region. One of the patients bitten by C. maculatus was drowsy, hypotensive and flaccid on admission but recovered without treatment. Mild or moderate local swelling, local lymphadenitis and mild fever were the only other features in this group. None of the patients bitten by Atractaspis had signs of systemic envenoming apart from moderate fever. Local blistering appeared in two cases but did not progress to necrosis. No patient showed any disturbance of blood coagulation, or evidence of spontaneous hemorrhage or of cranial nerve lesions. The small literature on the effects of Causus and Atractaspis venoms in man and in laboratory animals is reviewed. It appears that bites by these species are very unlikely to cause serious ill effects. A few deaths from Atractaspis bites have been reported, but the danger from these species has been exaggerated.